2022
DOI: 10.1039/d2fo02341e
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of sulforaphane on high-fat diet-induced metabolic associated fatty liver disease in mice via mediating the FXR/LXRα pathway

Abstract: Metabolic associated fatty liver disease (MAFLD) is becoming the key factor in causing chronic liver disease over the world. Sulforaphane (SFN) has been proved to be effective in alleviating many...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…122 The genes FXR, SHP, LXRα, and SREBP-1C are all associated with bile acid synthesis and metabolism. 123 Ma et al 124 conducted extensive research and discovered that SFN regulates bile acid synthesis and metabolism by upregulating the expression of genes such as FXR, SHP, and CYP7A1, while downregulating the expression of genes like LXRα and SREBP-1C. Additionally, Cardenia et al 125 fed mice with broccoli extract abundant in sulforaphane (BE) and found that BE inhibited cholesterol oxidation in the liver cells.…”
Section: ■ Potential Adverse Health Effects Of Copsmentioning
confidence: 99%
“…122 The genes FXR, SHP, LXRα, and SREBP-1C are all associated with bile acid synthesis and metabolism. 123 Ma et al 124 conducted extensive research and discovered that SFN regulates bile acid synthesis and metabolism by upregulating the expression of genes such as FXR, SHP, and CYP7A1, while downregulating the expression of genes like LXRα and SREBP-1C. Additionally, Cardenia et al 125 fed mice with broccoli extract abundant in sulforaphane (BE) and found that BE inhibited cholesterol oxidation in the liver cells.…”
Section: ■ Potential Adverse Health Effects Of Copsmentioning
confidence: 99%
“…Apart from activation of Nrf2, SFN was also shown to prevent high-fat diet (HFD)-induced NAFLD in mice by inhibiting NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome in liver through AMP-activated protein kinase (AMPK)-autophagy axis when administered with a daily dose of 30 mg/kg for 9 weeks along with HFD ( Yang et al, 2016 ). In recent years, the number of new mechanisms and molecular targets of SFN in the treatment of fatty liver reported by experimental studies has increased rapidly ( Figure 1 ), such as inhibition of lipogenic enzymes via ER stress-dependent decrease of X-box binding protein 1 (XBP1) expression and ER stress-independent blocking of sterol regulatory element binding protein-1c (SREBP1c) pathways ( Tian et al, 2018a ), alleviated ER stress through the upregulation of AMPK and peroxisome proliferators-activated receptor α (PPARα) ( Mansour et al, 2022 ), enhanced mitochondrial function via Nrf2 activation or promotion of mitochondrial biogenesis by peroxisome proliferator-activated receptor alpha co-activator pathway ( Lei et al, 2019 ), and regulation of FXR-mediated bile acid metabolism and LXRα-mediated fatty acid synthesis pathways ( Ma et al, 2022 ). SFN was also found to alleviate HFD-induced lipid deposition and suppress apoptosis by regulating the AMPK/SREBP1c/FAS signaling pathway both in vitro and in vivo ( Li et al, 2021 ).…”
Section: The Efficacy Of Sfn In the Treatment Of Liver Diseasesmentioning
confidence: 99%
“…BAs are important in lipid metabolism because they emulsify lipids, increase their interaction with lipase, and regulate the activity of pancreatic lipase and lipoprotein esterase. Consequently, BA enhances lipid hydrolysis metabolism in vivo [ 9 ]. BA produced by cholesterol catabolism facilitates the digestion and absorption of dietary lipids and actively participates in the regulation of lipid metabolism [ 10 ].…”
Section: Introductionmentioning
confidence: 99%